2019
DOI: 10.1007/978-3-030-29387-1_38
|View full text |Cite
|
Sign up to set email alerts
|

FittsFarm: Comparing Children’s Drag-and-Drop Performance Using Finger and Stylus Input on Tablets

Abstract: We used a two-dimensional Fitts' law task to compare finger and stylus input with children when performing drag-and-drop tasks on a tablet. Twentyeight children completed the study. Drag-and-drop performance was significantly better using a low-cost stylus compared to finger input. Throughput was 9% higher for stylus input (2.55 bps) compared to finger input (2.34 bps). Error rates were 35% percent higher for finger input (12.6%) compared to stylus input (9.3%). Error rates approximately doubled with smaller t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…We found that target size significantly affected task completion time and error rate in pointing tasks. When pointing at smaller targets, task completion time increased significantly over 30%, and error rate increased significantly over 75%, consistent with previous Fitts' Law studies on target size (Cassidy et al, 2019;Gillan & Bias, 2018;Groen et al, 2019;Lin et al, 2010). We also noticed that in the draggingand-dropping task, a larger target size produced a higher error rate, that is, with 55% more errors than a small target size.…”
Section: Target Size Effectsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that target size significantly affected task completion time and error rate in pointing tasks. When pointing at smaller targets, task completion time increased significantly over 30%, and error rate increased significantly over 75%, consistent with previous Fitts' Law studies on target size (Cassidy et al, 2019;Gillan & Bias, 2018;Groen et al, 2019;Lin et al, 2010). We also noticed that in the draggingand-dropping task, a larger target size produced a higher error rate, that is, with 55% more errors than a small target size.…”
Section: Target Size Effectsupporting
confidence: 90%
“…Input devices are essential computer accessories for fundamental operations (e.g., pointing and dragging) in human–computer interaction (HCI), especially with graphical user interfaces (GUIs) (Cassidy et al, 2019; Cockburn et al, 2012). While previous studies have compared several traditionally used input devices (e.g., mouse, touchscreen, and trackball) in pointing tasks (Chen & Or, 2017; Hertzum & Hornbæk, 2010; Natapov et al, 2009) and dragging tasks (Cassidy et al, 2019; Chen & Or, 2017; Cockburn et al, 2012; Wood et al, 2005), it remains unclear about the performance of some newly developed input devices operated by gestures (e.g., remote hand‐controller) (Jones et al, 2019). As compared with traditional ones, it could be fundamentally different to use these new input devices as no physical contract is required when using gestures to interact with GUIs.…”
Section: Introductionmentioning
confidence: 99%
“…remarked imposing a limit on the maximum distance of the dragging path would lead to a superior performance by children aged 3-6 years. In another study,Cassidy et al (2019) observed that for children aged 8 and 9 years the MT for drag and drop gesture does not vary significantly for finger-and stylus-based interactions. However, adequate research to establish the validity of Fitts' law for children of different age groups interacting with touchscreen devices has not been conducted.…”
mentioning
confidence: 91%
“…In both scenarios, Fitts’ law defines a linear relation between MT and ID e , whose slope usually quantifies the amount of information processed per second. Recent studies have investigated the user experience of children using touchscreen tablets, reporting a TP of around 2.3–2.5 bits/s [ 24 ], and complemented these findings with some recommendations for professionals who use these devices for teaching [ 25 ].…”
Section: Introductionmentioning
confidence: 99%